Plumbagin, a medicinal plant (lumbago zeylanica)‐derived 1, 4‐naphthoquinone, inhibits growth and metastasis of human prostate cancer PC‐3M‐luciferase cells in an orthotopic xenograft mouse model. Issue 3 (14th December 2012) - Hafeez, Bilal Bin; Zhong, Weixiong; Fischer, Joseph W.; Mustafa, Ala; Shi, Xudong; Meske, Louise; Hong, Hao; Cai, Weibo; Havighurst, Thomas; Kim, KyungMann; Verma, Ajit K.
Abstract : We present here first time that Plumbagin (PL), a medicinal plant‐derived 1, 4‐naphthoquinone, inhibits the growth and metastasis of human prostate cancer (PCa) cells in an orthotopic xenograft mouse model. In this study, human PCa PC‐3M‐luciferase cells (2 × 106) were injected into the prostate of athymic nude mice. Three days post cell implantation, mice were treated with PL (2 mg/kg body wt. i.p. five days in a week) for 8 weeks. Growth and metastasis of PC‐3M‐luciferase cells was examined weekly by bioluminescence imaging of live mice. PL‐treatment significantly (p = 0.0008) inhibited the growth of orthotopic xenograft tumors. Results demonstrated a significant inhibition of metastasis into liver (p = 0.037), but inhibition of metastasis into the lungs (p = 0.60) and lymph nodes (p = 0.27) was not observed to be significant. These results were further confirmed by histopathology of these organs. Results of histopathology demonstrated a significant inhibition of metastasis into lymph nodes (p = 0.034) and lungs (p = 0.028), and a trend to significance in liver (p = 0.075). None of the mice in the PL‐treatment group showed PCa metastasis into the liver, but these mice had small metastasis foci into the lymph nodes and lungs. However, control mice had large metastatic foci into the lymph nodes, lungs, and liver. PL‐caused inhibition of the growth and metastasis of PC‐3M cells accompanies inhibition of the expression of: 1) PKCϵ, pStat3Tyr705, and pStat3Ser727, 2) Stat3 downstream target genes (survivin and BclxL), 3) proliferative markers Ki‐67 and PCNA, 4) metastatic marker MMP9, MMP2, and uPA, and 5) angiogenesis markers CD31 and VEGF. Taken together, these results suggest that PL inhibits tumor growth and metastasis of human PCa PC3‐M‐luciferase cells, which could be used as a therapeutic agent for the prevention and treatment of human PCa. Highlights: ► Tumor growth and metastasis of human prostate cancer in an orthotopic xenograft mouse model. ► Expression of transformed oncogene (PKCε) and Stat3 in prostate tumors. ► Expression of Stat3 downstream target genes (BclxL and survivin). ► Expression of proliferative (ki67 and PCNA), angiogenesis (VEGF and CD31) and metastatic (MMP2, MMP9 and uPA) markers. ► We conclude that plumbagin may be used as a novel therapeutic agent against human prostate cancer metastasis.